Hepatitis B Infection Among Pregnant Women in China: A Systematic Review and Meta-Analysis - Liu, Dan; Liu, Yan; Ni, Jiaqi; Li, Hailong; Zeng, Linan; Zhang, Chuan; Zhang, Li; Yu, Qin; Wu, Bin; Zhang, Lingli (Frontiers in Public Health, 2022)
Background: A study of the current situation and characteristics of hepatitis B virus (HBV) infection among Chinese pregnant women is meaningful to provide baseline information for future research and policy making, aiming to eliminate HBV in China. Objectives: To provide the epidemiological status of HBV infection among pregnant women in China. Methods: PubMed, EMbase, The Cochrane Library, and three Chinese databases were searched. Cohort studies and cross-sectional studies on HBV prevalence in Chinese pregnant women published after 2016 were retrieved. In addition, combined HBV prevalence and 95% confidence interval were calculated. This research was registered in PROSPERO (CRD42021289123). Main results：42 studies were included in the study, with a sample size of 4,007,518 cases, and 20 provinces in China. The prevalence of HBV in Chinese pregnant women was 6.64% (95% CI 5.72-7.57%) during the period between 2016 and 2021. Among HBsAg positive pregnant women, the HBeAg positive rate was 25.80% (95% CI 22.26-29.69%). Moreover, geographic regions with HBV prevalence ranking from high to low were in western China, eastern China, and central China successively. Conclusion: The prevalence of HBV in Chinese pregnant women is intermediate endemic, although disparities exist between different regions. Among pregnant women with HBV infection, a high proportion of the patients have strong infectivity. Factors affecting HBV prevalence remain controversial, which demands further studies.